Optimization of CO2 geological storage sites based on regional stability evaluation—A case study on geological storage in tianjin, china - Lv, Tianxue; Wan, Jianhua; Zheng, Yajie; He, Lusheng; Yi, Lixin (Frontiers in Earth Science, 2022)
Carbon dioxide geological storage is one of the important means to mitigate greenhouse effect and curb global warming. The key to carbon dioxide (CO2) geological storage is to select a suitable storage site. Using the geological analysis method and Analytic Hierarchy Process (AHP)-fuzzy comprehensive evaluation method, combining the qualitative analysis of geological conditions with the quantitative calculation of site parameters, this paper determines a site target area suitable for CO2 geological storage in Tianjin. Firstly, the regional crustal stability of Tianjin is discussed, and the characteristics of regional gravity field anomaly, regional crustal thickness and regional aeromagnetic characteristics are comprehensively analyzed. The site is focused on Banqiao sag, a class ⅳ tectonic unit in Bohai Bay Basin; Secondly, aiming at the storability, safety and economy of the site, the expert investigation method is used to construct the target area evaluation index system, including 4 primary indexes and 10 secondary indexes. The weight of each index is determined by analytic hierarchy process. A two-level fuzzy comprehensive evaluation mathematical model is constructed. The suitability of CO2 geological storage in three site (site A, site B, site C) in Banqiao sag is evaluated. The results are as follows: the comprehensive membership of site A, site B and site C are 0.8629, 0.3926 and 0.1750 respectively. The comprehensive membership of site A is the largest. The evaluation results show that the preferred target area of Tianjin local carbon dioxide geological storage site is located in ‘site A’ near Dazhangtuo fault in Banqiao sag, Huanghua depression, Bohai Bay Basin (with an area of about 5 km2). In this paper, a suitable target area is delineated for the local CO2 geological storage site in Tianjin, which can be used as an advantageous location for CO2 geological storage. The conclusion has a positive response to the problem of CO2 emission reduction in Tianjin.